ANALYSIS OF DPR POLICY IN THE PERIOD OF OFFICE OF THE VILLAGE HEAD - Sopiah Indah Daulay; Ramadani Ramadani (Jurnal Syntax Transformation, 2023)
The House of Representatives (DPR) as a policy-making institution contained in the form of laws and is a strategic institution that regulates the entire life of the Indonesian people. However, if studied in fiqh siyasah, the concept of caliph (leader) is allowed to serve as long as possible if he can carry out the mandate as stipulated in Islam. In article 39 paragraphs (1) and (2) of Law number 6 of 2014 concerning the term of office of village heads. That the position of village head which was originally 6 years 3 periods was changed to 9 years 2 periods. This raises problems related to the limitation of the power of public office and the occurrence of KKN (corruption, collusion, and nepotism) during the tenure of the village head. This research uses Normative Law research or legal research that views humuk as a norm system building. The method carried out by the author is in the form of collecting sentences both scientific papers, notebooks, approaches to laws and regulations, relevant journals. The results of this study are to avoid conflicts between communities in the election of elected and unelected village heads and to focus on the kineja of village development. Because the regeneration or transition of the term of office of the village head in the community is needed in the context of organizing ideas and ideas about village development.